How Accurate is whosampled.com?: Exploring the reliability of a user-generated resource - Orosz, Jeremy (Empirical Musicology Review, 2023)
Whosampled.com is a website that hosts user-compiled lists of samples, covers, and remixes of pre-existing music. This article will evaluate the accuracy of the information on whosampled.com through cases studies on the music of Bruno Mars, Janelle Monáe, Dua Lipa, and the reported samples of Classical music, to determine which types of entries are most likely to be accurate and why. While the site is an informative resource for exploring clear examples of direct samples in genres like hip hop, it is less reliable in documenting other forms of borrowing, especially in genres in which digital sampling is not commonly practiced.